Synergism of Anti-Malarial Effect of Carica papaya L. and Moringa oleifera Leaf Extracts in Mice - Yusuf, Yenni; Asri, Rangga Meidianto; Go, Rivaldo; Zuhair, Muhammad Naufal; Kaharuddin, Kania Meliani; Parenden, Martrisna Dara Karnia; Saputra, Mesakh Diki; Elim, Diany; Banjar, Muhammad Fadhil; Hartono, Hartono (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Malaria parasites, Plasmodium spp, can develop resistance to anti-malarial drugs. Hence, potential alternative therapeutic agents should be explored. This research aimed to investigate the anti-malarial effect of a combination of Carica papaya and Moringa oleifera leaf extract. Peter’s test performed on Balb/c mice to investigate the malarial parasite growth inhibition. Mice were infected with Plasmodium berghei by intraperitoneal injection to provoke rodent malaria. After infection, we grouped every 5-6 mice into different treatment groups, including a negative control group, a positive control group treated with artesunate, a moringa group, a papaya group, and a combination therapy group. Treatments were initiated 3 hours after infection (day 0) and continued every day until day 3. On day 4, we examined a thin smear of the tail vein blood for parasitemia to calculate the suppression rate. The result shows that the parasite suppression rate of C. papaya leaf extract (CPLE) is 15.02 % (percent parasitemia 4.56±1.96), the suppression rate of M. oleifera leaf extract (MOLE) is 17.32% (percent parasitemia 4.44±1.78) and that of the combination extract (CE) is 28.73% (percent parasitemia 3.82±1.48). In conclusion, there is a synergism of the anti-malarial effect of the combined leaf extract of C. papaya and M. oleifera.